Availability and Utilisation of Library-based Online Resources for Learning Activities by Undergraduates of University of Ibadan, Nigeria (2019)
Library-based online resources are important due to their enormous benefits to students and university libraries. In particular, they offer students the opportunity to access current and relevant information from different subject areas. The purpose of this study was to investigate the availability and use of these resources for learning activities by undergraduates of the University of Ibadan, Nigeria. Descriptive survey design was adopted for the study and the population consisted of 12,173 full-time undergraduates. Stratified, proportionate, random sampling techniques were used, with a sampling fraction of 2.5%, to obtain a sample size of 303 students. The data collection instrument was the questionnaire titled “Availability and Utilization of Library-Based Online Resources For Learning Activities By Undergraduates (AULORLAU)” and data were analyzed using descriptive and inferential statistics consisting of frequency, tables and percentages for the research questions, while Pearson Moment Correlation was used to analyse the hypothesis at 0.05 level of significance. The findings revealed that electronic journals were the most available (mean=2.9) and frequently (mean=3.3) used Library based online resources among the undergraduates and ‘assignment’ was the main purpose for which they used these resources, while poor internet connectivity was their greatest challenge. There was significant relationship between availability of the resources and their utilization by the students (r=0.197; p<.05). Library-based online resources enhanced students’ learning in all academic disciplines, as the resources provided lecturers and students alike with vast quantities of information in an easily accessible non-sequential format. The study therefore recommended, among others, that university administrators and library management should make efforts to improve on bandwidth and enhance connectivity within the library premises so as to enable students have easy access to the Internet.